Stability, Liquidity, Efficiency, and Profitability After Spin-off Implementation: Evidence from Indonesian Islamic Banking Industry - Panca, Aqilla Dhianir Rahman; Sudrajad, Oktofa Yudha (Journal Integration of Management Studies, 2023)
The business-unit Islamic bank was forced to separate from its parent company according to Banking Act No. 21 of 2008 that issued by the Indonesian Central Bank. However, the Development and Strengthening of the Financial Sector Act No.4 of 2023 have allowed them not to convert themselves into full-fledged Islamic banks with certain conditions. Thus, doing spin-offs will be appealing if it is beneficial for them. However, the benefit of converting a business-unit Islamic bank spin-off into a full-fledged Islamic bank has yet to be entirely evident. This study aims to determine how spin-off affects the stability and financial performance, covering the profitability, efficiency, and liquidity of spin-off business-unit Islamic banks in Indonesia. Using difference-in-difference (DID) analysis, this study examined four spin-off full-fledged Islamic banks as the treatment group and twenty business-unit Islamic banks as the control group from 2005 to 2019. The parameter used are return on equity (ROE), cost-to-income ratio (CIR), financing-to-deposit ratio (FDR), quick ratio (QR), and Z-score. The result indicates that profitability and efficiency are decreasing, while the liquidy kept increasing after the spin-off undertaking. However, the stability has not been found to have evidence of significant differences after spin-off implementation.